SENSORY PERCEPTION DEFICITS IN SCHOOL AGE CHILDREN - McFall, Christine K. (Acta Scientiae et Intellectus, 2024)
The ability to receive, process, interpret, then react to stimuli is the primary function of the sensory perception system; a component of the individual’s neurological system. Deficits in a student’s sensory perception system affect his or her ability to function in numerous environments, including school. The literature reviewed in this paper will explore the sensory perception concept as it applies to school age children. Auditory and visual perceptions are known and understood by many professional school staff. Therefore, knowledge regarding the other senses will be explored at more length in this paper. Limited interventions for students with sensory perception deficits and sensory processing disorders will be suggested, but need to be customized to the educational needs of the child.